Brinquedo terapêutico como tecnologia do cuidado em pediatria: conhecimento de acadêmicos de enfermagem - FONSECA, Andressa Fabiana Ferreira (2019)
Therapeutic toy is an auxiliary tool in the nursing work process and is a strategy in the interventions of the team. It promotes the relief of anxiety, fear and frustration, as well as, it enables communication, expression of feelings and favors the creation of a link between professional, academic, child and family. In view of the relevance and benefits of therapeutic toy in pediatric care, it is perceived the need for nursing undergraduate courses to employ the teaching of the subject, assuring the theoretical and practical experience of this instrument. Thus, to train nursing professionals who are humanized and instructed to use therapeutic toy in care. The study analyzed the nursing students' knowledge about the use of therapeutic toy in the pediatric unit. Is based on a descriptive, cross-sectional study with a qualitative approach on nursing students' knowledge about therapeutic toy as a technology for hospitalized child care. The subjects of the research were thirteen academics from the 6th and 7th semester of the Faculty of Nursing of the Federal University of Pará (FAENF / ICS / UFPA), located in Belém of Pará. They met the inclusion criteria and accepted to participate of the study after the presentation of the informed consent form. Data were collected through an open interview, using a semi-structured script and recorded with the help of a mobile recorder. The study was carried out from October 24 to November 1, 2018. The research was approved by the Research Ethics Committee of the Health Sciences Institute of the Federal University of Pará (ICS / UFPA), in accordance with resolution 466 / 12 of the National Health Council. Data analysis was performed through content analysis of interviews, where the following categories emerged: Conceptualization of therapeutic toy as a tool for nursing care, benefits and importance for hospitalized children, factors that interfere with the applicability of therapeutic toy and inclusion of therapeutic toy in educational grade. The results showed that therapeutic toy is a beneficial and effective tool in the treatment of hospitalized children, providing greater interaction and trust between professional / patient / family and better coping with their hospitalization, but some difficulties in applying it are found. He pointed out that therapeutic toy helps academics to have better skills with children. Thus, it was verified the relevance in addressing this subject in the undergraduate and inserting it in the curricular grid of the nursing courses, because it allows the formation of more humanized and sensitized professionals to implement BT in their future routine of pediatric care, seeking to offer a more holistic care.